Exact solutions for equations of flow and heat transfer in fluid saturated porous media - ADANHOUNME, VILLÉVO; OLODO, E. (My University, 2014)
In this paper we investigate the complete behavior of the viscous and incompressible fluid flow in an anisotropic saturated porous horizontal cavity. Taking into account the rigid/rigid and stress-free/stress-free horizontal boundaries, we obtain the exact solutions for flow and heat transfer equations, i.e. the velocity and temperature, depending on the Darcy– Rayleigh number, the Darcy number, the anisotropic permeability ratio and the inclination of the principal axis. These obtained variables allow us to compute the different expressions of the pressure gradient.
Keywords: Boundary conditions · Convection · Porous matrix · Pressure gradient